Disability research a review - Camara, Erlinda F. (Education quarterly.)
The review of contemporary disability research focus on three major areas. The first treats policy analysis as an area of investigation advocated by Dror (1971), Dror (1971a), Anderson (1975), Dye (1976) and Dunn (1971). The second addresses itself to the prevention, treatment and rehabilitation of disabilities and disabled persons. The third focuses on attitudes shown the physically disabled by the service providers, the employers, the disabled themselves, their families, and the variables pertinent to these attitudes.